2014
DOI: 10.4236/ijohns.2014.31004
|View full text |Cite
|
Sign up to set email alerts
|

Tracheoesophageal Voice Prosthesis Outcomes: Success or Insucess?

Abstract: Introduction: Total laryngectomy/pharingo-laryngectomy is a potentially aggressive surgery for advanced laryngeal/hypopharyngeal carcinomas, which results in important physical and functional changes that compromise some of the most vital functions, including speech communication. For these patients, tracheoesophageal speech is considered to be the gold standard for voice rehabilitation. Objectives: The purpose of the present study was to determinate the success rate of voice prosthesis rehabilitation, voice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…The prosthesis device life can also vary across regions due to number of reasons, including diet, patient preference, reimbursement and voice expectations, and tolerance of periods of minor leakage prior to replacement. The life of the voice prosthesis has been reported to be anywhere between 2 and 14 months based on the different group of patients, devices, and regions studied [10,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prosthesis device life can also vary across regions due to number of reasons, including diet, patient preference, reimbursement and voice expectations, and tolerance of periods of minor leakage prior to replacement. The life of the voice prosthesis has been reported to be anywhere between 2 and 14 months based on the different group of patients, devices, and regions studied [10,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cornu et al who reported device life of 303 days in a South African patient population describe this phenomenon as patients taking Ba more conservative approach^and this may have contributed to longer mean device life [32]. In a review by Sara Cruz et al in Portugal, mean device life were 1-74 months for primary prosthesis and 1-24 months for secondary prosthesis [33]. Two Indian studies reported mean prosthesis longevity of 18 and 15 months, respectively [25,44].…”
Section: Discussionmentioning
confidence: 99%
“…Airflow through the esophageal structure will generate a new fundamental tone that, as with the esophageal voice, will later be converted into speech sounds. The use of a voice prosthesis for communication requires daily maintenance and needs to be replaced approximately every 6 months, (130)(131)(132) The rate of complications can range from 15 to 72% (132), being the most frequent the leak through de voice prosthesis and the leak around the tracheoesophageal prosthesis.…”
Section: -Tracheoesophageal Speech (Voice Prosthesis)mentioning
confidence: 99%
“…Формирование трахеопищеводного шунта осу-ществляют как за счет собственных тканей пациента, так и с применением силиконовых эндопротезов [29,[51][52][53][54][55][56][57][59][60][61][62]. Разработка операций по трахеопище-водному шунтированию за счет аутотканей была на-правлена на формирование защитного клапанного механизма.…”
Section: ларингэктомия с трахеопищеводным шунтированием и эндопротезиunclassified
“…F. J. Hilgers приводит данные о том, что длительность эксплуатации первых протезов Provox составила от 6 нед до 2 лет, а средний срок службы -5 мес. Поэтому дальнейшие исследова-ния были направлены на увеличение сроков эксплуа-тации голосовых протезов путем механического удале-ния остатков пищи, мокроты, обработки протезов противогрибковыми и антисептическими препаратами [29,[51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: ларингэктомия с трахеопищеводным шунтированием и эндопротезиunclassified